Science transformed? A comparative analysis of 'societal relevance' rhetoric and practices in 14 Canadian Networks of Centres of Excellence. (1st June 2016) - Coutinho, Aline; Young, Nathan
Abstract : One of the most hotly debated ideas in science studies is the claim that contemporary science is in the midst of a transformation. While 'transformationalist' arguments and concepts vary, their core principle is that the norms, values and practices that have enforced the separation of science from society are being challenged by new expectations that scientists pursue closer connections with industry, government and/or civil society, and address research questions of immediate value to non-academic partners. While many major funding agencies have embraced this idea and now pressure scientists to enhance the 'societal relevance' of their work, the impact of these changes on scientific practices is still unclear. This paper reports findings from a comparative meso-level analysis of 14 large Canadian research networks funded by an agency with an explicit transformationalist mandate - the Networks of Centres of Excellence (NCE) programme. Documents and web communications from these 14 NCEs, as well as from the central programme administration office, are analysed and compared to key transformationalist concepts, such as Mode 2 science, post-normal science, the triple helix model, academic capitalism and strategic science. We find that transformationalist ideas have a strong rhetorical presence across the 14 NCE projects and the central office, but that a great deal of inconsistency and confusion exists at the level of implementation and assessment of outcomes. Easily quantifiable outputs, such as the commercialization of research findings, are favoured over softer qualitative outcomes, such as public engagement and knowledge sharing. We conclude by arguing that the NCE programme is having an observable impact on the rhetoric of science, but any resulting transformations in practice are incremental rather than radical.